Harry Potter and the Order of the Phoenix - Rowling, J. K. (Rowling, J. K. Harry Potter series, 2022)
As Harry faces his upcoming fifth year at Hogwarts Academy, there are increasing rumors of dark times coming and of Lord Voldemort's return to power, and a secret anti-Voldemort society, The Order of the Phoenix, begins meeting again.